Inovasi Pelayanan Publik Melalui Aplikasi “Durenmas” Oleh Dinas Kependudukan & Pencatatan Sipil (Dindukcapil) Kabupaten Banjarnegara - Eva Agus Triana; Lina Aryani (Jurnal Pemerintahan dan Politik, 2021)
This research is motivated by the complexity of service problems at the Department of Population and Civil Registration (Dindukcapil) of Banjarnegara Regency during the 2016-2020 period. The purpose of this research is to analyze the usefulness of the application "Durenmas" as an innovation in information technology-based public services in the digitalization era and to find out the strategies used to attract users to switch to online services. The research method used is qualitative by using a descriptive-qualitative approach to describe the analysis of service innovation indicators according to Rogers (1983) public service which includes (1) relative advantage, (2) compatibility / contextuality; (3) complexity; (4) observability; and (5) can be tried (triability) through observation data collection techniques, in-depth interviews and documentation. The results showed that almost all of the five indicators of public service innovation were fulfilled. The slogan "Dindukcapil Banjarnegara Ora Leren Serve the Community" becomes a strong foundation in optimally implementing service innovations as a form of optimal service innovation implementation so that great effort is needed through regular evaluation and appropriate maintenance.Keywords : Administration; Public Service Innovation; Durenmas